If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42=12+5(x-1)
We simplify the equation to the form, which is simple to understand
42=12+5(x-1)
Reorder the terms in parentheses
42=12+(+5x-5)
Remove unnecessary parentheses
+42=+12+5x-5
We move all terms containing x to the left and all other terms to the right.
-5x=+12-5-42
We simplify left and right side of the equation.
-5x=-35
We divide both sides of the equation by -05 to get x.
x=7
| 192=72x^2+24X | | 6(x+3)-75=5(x-10) | | 5-5x=-8x+14 | | (12-15)3= | | 192=72x^2+24 | | 2x+3(x-4)=(x-3) | | A+BX=CX+D | | 4(Z+7)-6=2 | | 29-(-q)=86 | | xsquared+8x-5=15 | | g-13.37=-23 | | (0.5)(y)=3 | | 5y=175 | | 3(x-1)+60=8(x+4) | | g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) |